RamR is not involved in the regulation of ramA associated antibiotic resistance in Salmonella enterica serovar Typhi. (October 2017) - Miao, Minhui; Cao, Wei; Wang, Hongxia; Yan, Jieting; Wang, Min; Zheng, Yi; Xie, Xiaofang; Zhang, Xia; Zhang, Haifang; Du, Hong
Abstract: RamA, a global transcriptional activator, belongs to the AraC/XylS family of regulatory proteins and can regulate multidrug resistance through activating the expression of AcrAB. In Salmonella spp., Klebsiella pneumonia, Enterobacter cloacae and Enterobacter aerogenes, RamR represses the transcription of gene ramA through binding to the upstream sequences of ramA . In this study, we found that the locus and transcription directions of ramA - ramR in S. Typhi GIFU10007 are different from that in S. Typhimurium (SL1344). To study the role of RamR involved in regulation of ramA in S. Typhi, we constructed ramA over-expression strain and ramR deletion mutant, and detected the expression level of ramA, and measured the growth curve of these strain in the presence of ampicillin. The results showed that RamR in S. Typhi neither repressed the expression of ramA, nor affected the bacterial resistance to ampicillin. In summary, RamR is not the repressor of RamA in S. Typhi, which is different from its role in other bacteria, such as S . Typhimurium and K. pneumoniae .